2010
DOI: 10.1186/1471-2164-11-134
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for intra-experiment variation in Illumina BeadChip data is necessary to generate robust gene-expression profiles

Abstract: BackgroundMicroarray technology is a popular means of producing whole genome transcriptional profiles, however high cost and scarcity of mRNA has led many studies to be conducted based on the analysis of single samples. We exploit the design of the Illumina platform, specifically multiple arrays on each chip, to evaluate intra-experiment technical variation using repeated hybridisations of universal human reference RNA (UHRR) and duplicate hybridisations of primary breast tumour samples from a clinical study.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 42 publications
1
27
2
Order By: Relevance
“…Pre-and post-dex samples from the training and the test cohort were processed within a single run each (that is, RNA amplification, hybridization and scanning). To further reduce the described batch effects for Illumina arrays (Kitchen et al, 2010) pre-and post-dex RNAs were hybridized to the same chip for each individual, and cases and controls were randomized across arrays and arrays positions.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-and post-dex samples from the training and the test cohort were processed within a single run each (that is, RNA amplification, hybridization and scanning). To further reduce the described batch effects for Illumina arrays (Kitchen et al, 2010) pre-and post-dex RNAs were hybridized to the same chip for each individual, and cases and controls were randomized across arrays and arrays positions.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate potential batch effect, an empirical Bayes methodology implemented in ComBat software 41 was applied to all data from each of the different chips to effectively remove batch effects in the experiment. 42,49 Analysis of variance (ANOVA) was conducted to evaluate the batch effects for normalized β values and showed that about 96% of CpG sites had significant batch effects before normalization, but this proportion dropped to 0.12% after normalization using ComBat. All of the analyses were based on methylation levels after performing considering gender, two time points, CpG islands and gene structures.…”
Section: Methodsmentioning
confidence: 99%
“…Before biomarker discovery analysis or hierarchical clustering, batch correction (ComBat [16]), positive control sum normalization, background subtraction (with counts ,1 changed to 1), sum normalization, and log 2 -transformation were performed (Bioconductor [17]). …”
Section: Treg-specific Demethylated Region Analysismentioning
confidence: 99%